Seeing is believing: Educating through a gender lens - Elizabeth Carriere (Adult Education Research Conference, 1995)
Drawing on feminist perspectives, the author positions policy analysis as an activity that has significant impact on the lives of women, and the attainment of equality. The gender lens project is described as an experimental application of feminist adult education principles in a government setting.